Importance of Battery Recycling & Swapping: The Next Inevitable Step in EV Supply Chain - Ajay Serohi (International Journal of Supply Chain Management, 2021)
Purpose: The purpose of this study is to fathom the importance of battery supply chain including battery swapping and recycling as well as the charging infrastructure as nodes in the electric vehicle (EV) supply chain in India. It also delves into the ways in which Faster Adoption and Manufacturing of Hybrid and Electric Vehicles or FAME II is addressing these issues.Literature Review: One of the key obstacles in the way to the speedy adoption of EVs is range anxiety. A healthy and expanding network of charging infrastructure has a very important role to play in penetration and propagation of E-mobility. Fame II is also committed towards creating charging infrastructure besides providing demand incentive. The problem of battery waste generation which is an obvious fall out of e-mobility adoption is intended to be addressed through battery recycling and battery swapping – both are at a nascent stage in India with significant potential for growth.Design/ Methodology/ Approach: The study looks into both primary data (gathered through survey) and secondary data (collected from authentic data sources both public and private) sources. The mix of empirical research and direct face-to-face interview with consumers helps to better substantiate our argument.Findings: Adoption of E-mobility is unavoidable so is battery waste generation. Battery recycling and battery swapping can be the two technologies that assume enormous importance with the expansion of EV market in India. Range anxiety, another key concern of the potential and present EV owners, can be taken care of by ramping up charging infrastructure – a key area of focus of the Indian Government in its FAME I II schemes.